Hypercapnia-induced active expiration increases in sleep and enhances ventilation in unanaesthetized rats - Leirão, Isabela P. [UNESP]; Silva, Carlos A. [UNESP]; Gargaglioni, Luciane H. [UNESP]; da Silva, Glauber S. F. [UNESP] (Wiley, 2018)
Key points: Expiratory muscles (abdominal and thoracic) can be recruited when respiratory drive increases under conditions of increased respiratory demand such as hypercapnia. Studying hypercapnia-induced active expiration in unanaesthetized rats importantly contributes to the understanding of how the control system is integrated in vivo in freely moving animals. In unanaesthetized rats, hypercapnia-induced active expiration was not always recruited either in wakefulness or in sleep, suggesting that additional factors influence the recruitment of active expiration. The pattern of abdominal muscle recruitment varied in a state-dependent manner with active expiration being more predominant in the sleep state than in quiet wakefulness. Pulmonary ventilation was enhanced in periods with active expiration compared to periods without it. Abstract: Expiration is passive at rest but becomes active through recruitment of abdominal muscles under increased respiratory drive. Hypercapnia-induced active expiration has not been well explored in unanaesthetized rats. We hypothesized that (i) CO2-evoked active expiration is recruited in a state-dependent manner, i.e. differently in sleep or wakefulness, and (ii) recruitment of active expiration enhances ventilation, hence having an important functional role in meeting metabolic demand. To test these hypotheses, Wistar rats (280–330 g) were implanted with electrodes for EEG and electromyography EMG of the neck, diaphragm (DIA) and abdominal (ABD) muscles. Active expiratory events were considered as rhythmic ABDEMG activity interposed to DIAEMG. Animals were exposed to room air followed by hypercapnia (7% CO2) with EEG, EMG and ventilation (VE) recorded throughout the experimental protocol. No active expiration was observed during room air exposure. During hypercapnia, CO2-evoked active expiration was predominantly recruited during non-rapid eye movement sleep. Its increased occurrence during sleep was evidenced by the decreased DIA-to-ADB ratio (1:1 ratio means that each DIA event is followed by an ABD event, indicating a high occurrence of ABD activity). Moreover, VE was also enhanced (P < 0.05) in periods with active expiration. VE had a positive correlation (P < 0.05) with the peak amplitude of ABDEMG activity. The data demonstrate strongly that hypercapnia-induced active expiration increases during sleep and provides an important functional role to support VE in conditions of increased respiratory demand.
Keywords: breathing control; EEG; EMG; expiratory activity; sleep; wakefulness